Gene Expression Array Analyses Predict Proto-Oncogene Expression During Perineural Invasion in Pancreatic Ductal Adenocarcinoma - Zhao, Shu; Xue, Zhen; Wang, Jing-Yao; Song, Peng (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Pancreatic ductal adenocarcinoma is the tumor type with the highest incidence of perineural invasion. This study tries to identify the differentially expressed genes regulated between pancreatic ductal adenocarcinoma tissues with perineural invasion and without perineural invasion. Materials and Methods: The GSE102238 profile was downloaded. Gene function and pathway analysis were subsequently conducted. A protein–protein interaction network was constructed to search for hub genes. Both univariate Cox analysis and multivariate Cox analysis were calculated to identify prognostic factors. Quantitative real-time polymerase chain reaction (RT-PCR) and overall survival analysis of hub genes were used to verify. Results: Our study identified 242 differentially expressed genes including 68 upregulated differentially expressed genes and 174 down regulated differentially expressed genes, which were involved in important functions and pathways. Nine relevant core genes using protein–protein interaction analysis as well as nestin (NES)/vascular endothlial growth factor (VEGF) signaling pathway which is highly related to the pathological process of perineural invasion in pancreatic ductal adenocarcinoma were also discovered. The differentiation was identified as an independent prognostic factor (P < .05) after multivariate Cox analysis. Three upregulated genes (JUP, CALM1, and NES) and 6 downregulated genes (EPHA2, ARF1, ORM2, TERT, IL18, and CXCL3) were validated by quantitative RT-PCR and they all had markedly worse overall survival (P < .05). Conclusion: This analysis showed that 9 core genes including JUP, CALM1, NES, EPHA2, ARF1, ORM2, TERT, IL18, and CXCL3, as well as NES/VEGF signaling pathway, have a relationship with the development process of perineural invasion in pancreatic ductal adenocar cinoma. Cox analysis and overall survival analysis suggested differentiation as an independent prognostic factor and key roles for these 9 hub genes in perineural invasion prognosis in pancreatic ductal adenocarcinoma. Cite this article as: Zhao S, Xue Z, Wang J, Song P. Gene expression array analyses predict proto-oncogene expression during perineural invasion in pancreatic ductal adenocarcinoma. Turk J Gastroenterol. 2024;35(1):48-60.